Pengaruh metil eugenol block plus terhadap tangkapan lalat buah Bactrocera spp. pada tanaman cabai di Desa Lembang, Kecamatan Lembang, Kabupaten Bandung Barat - Agus Susanto; Agus Dana Permana; Sri Hartati; Tohidin; Desy Natalia Br. Saragih (Jurnal Entomologi Indonesia, 2021)
Fruit fly Bactrocera spp. is one of important pests in chili pepper. The use of methyl eugenol (ME) block plus as an attractant in traps is one method of controlling fruit flies populations. This study aims to find out the appropriate formulation of ME block plus formulation in increasing fruit fly catches on chili pepper. The experiment was carried out from January to April 2018 in Lembang Village, Lembang District, West Bandung Regency. The experiment used a randomized block design consists of eight treatments and three replications. The treatments tested were ME 2 ml was applied to all treatments using cotton; block; chili essence 4 ml block; 4 ml block of guava essence; orange essence 4 ml block; starfruit essence 4 ml block; mango essence 4 ml block; an attractant block product with the active ingredient ME. Although the results showed that all the treatments tested could not attract female fruit flies, the essence formulation was successful in attracting male fruit flies by 87%. The 4 ml chili essence in the 2 ml ME block formulation was the most effective treatment to increase male fruit fly catches by as much as 377 fruit flies/traps/week specifically the species Bactrocera dorsalis (Hendel), Bactrocera carambolae Drew & Hancock, Bactrocera umbrosa Fabricius, and hybrid fruit flies B. dorsalis x B. carambolae.